2017
DOI: 10.1021/acs.orglett.6b03864
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Reactivity of Thermally Stable Anhydrous Quaternary Ammonium Fluorides

Abstract: The synthesis and properties of a new class of anhydrous quaternary ammonium fluorides, based on the rigid skeleton azabicyclo[2.2.2]octane, is described. Compounds 2a-d were easily prepared by passing the corresponding ammonium iodides over fluoride-based resin followed by drying their hydrated form at 100 or 140 °C under reduced pressure. The stability (experimental and theoretical study), solubility, reactivity, and characterization by solution and solid-state MAS NMR are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 22 publications
0
18
1
Order By: Relevance
“…[1][2] "Naked fluoride" refers to dehydrated (or desolvated) fluoride ions. While gaseous naked fluoride is known, 3 naked fluoride does not exist in water (or other solvents), as analogous to H + in water, fluoride is always hydrated, or otherwise closely associated with its cation; 4 if it could be prepared, liquid phase naked fluoride would be extremely basic and have immense catalytic activity. [3][4][5][6] The relative "nakedness" of fluoride is strongly affected by the cation size; the larger size of the cation, the more weakly it associates with the fluoride, and the more naked the fluoride becomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2] "Naked fluoride" refers to dehydrated (or desolvated) fluoride ions. While gaseous naked fluoride is known, 3 naked fluoride does not exist in water (or other solvents), as analogous to H + in water, fluoride is always hydrated, or otherwise closely associated with its cation; 4 if it could be prepared, liquid phase naked fluoride would be extremely basic and have immense catalytic activity. [3][4][5][6] The relative "nakedness" of fluoride is strongly affected by the cation size; the larger size of the cation, the more weakly it associates with the fluoride, and the more naked the fluoride becomes.…”
mentioning
confidence: 99%
“…6,[8][9][10] Fluoride is only stable with organic cations that lack β-hydrogens, such as tetramethylammonium fluoride (TMAF), 9 or cations like azabicyclo[2.2.2]octane, where the β-hydrogen is sterically hindered towards elimination. 3 However, to produce naked fluoride requires dissolution of these salts in dry aprotic solvents, in which their solubility is very low. Conceivably, these salts could be employed in molten form, but they most likely have high melting point or decompose without forming a liquid phase (decomposition temperature: 170 °C for TMAF and 140 °C for azabicyclo[2.2.2]octane fluoride).…”
mentioning
confidence: 99%
“…The key factor enabling them to behave as sources of "naked" fluoride is the presence of a shell of methyl hydrogen atoms in the countercation that shelters its positive charge, thus weakening the electrostatic attraction to the fluoride anion. Conversely, these salts lack antiperiplanar β-hydrogen atoms susceptible to undergoing Hofmann (E2) elimination with the fluoride anion (Scheme 3c), such as TMAF (1) [55], N,Ntrimethyl-1-adamantylammonium fluoride (2) [61], 1,1,3,3,5,5-hexamethylpiperidinium fluoride (3) [62], N-1-methylhexamethylenetetramine, fluoride (MHAF) (4) [63], tetramethylphosphonium fluoride (TMPF) (5) [64], hexamethylphosphazenium fluoride (6) [65], acyl azolium fluoride (7) [66], and more recently, azabicyclo [2,2,2]octane (8) (Scheme 3b) [67]. Additionally, DiMagno and co-workers demonstrated that the inherent instability of anhydrous tetrabutylammonium fluoride (TBAF) (11)-due to the presence of β-hydrogen atoms-can be circumvented by carefully treating hexafluorobenzene (12) in situ with tetrabutylammonium cyanide in polar aprotic solvents at sub-zero temperatures (Scheme 3d) [68].…”
Section: "Nakedness" Of the Fluoride Anionmentioning
confidence: 99%
“…Christe and co-workers reported the first truly stable anhydrous organic cation fluoride salt by dehydrating tetramethylammonium fluoride ([TMA]F). 1 Subsequently, several organic cations have been combined with F − including tetrabutylammonium ([TBA]F), 4 N-methylquinuclidinium, 5 tetramethylphosphonium, 6 ([TMP]F), and (L Dipp )H + (L Dipp = 1,3-bis(2,6-diisopropylphenyl)-1,3dihydro-2H-imidazol-2-ylidene) 7 . [8][9][10][11] Reactive and highly basic F − combined with an organic cation is often used to increase the solubility of an inorganic fluorocomplex or to stabilize the anion of a weakly Lewis acidic parent fluoride (weak fluoride ion acceptor).…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Most organic cations are unstable when combined with F − . Such salts are hard to isolate due to β-hydrogen elimination, 1,[27][28][29] although this can be avoided with [TMA]F because the β-hydrogen atoms are absent (as in the exceptional case of N-methylquinuclidinium salt) 5 . Reactive anhydrous F − is sometimes created in an unusual way, as in the in situ generation of [TBA]F from hexafluorobenzene and [TBA]CN.…”
Section: Introductionmentioning
confidence: 99%